Treatise on an alternative perspective on the two-process model of sleep regulation - Frederik Bes (npj Biological Timing and Sleep)
Abstract The two-process model of sleep regulation, groundbreaking for the field of sleep research, describes sleep-wake behavior as regulated by the interaction of a homeostatic sleep-wake drive, process S (‘sleep debt’), and a circadian pacemaker process C, that “gates” S between two thresholds. The model has achieved great acceptance and application. The conception of the model would have been fundamentally different if one of the model’s creators (Borbély) had retained an alternative conceptual perspective, which he initially described at the time but did not elaborate on. The alternative considers the interaction of two sleep-wake processes more or less equivalent in strength and would a) allow the integration of REM sleep as an important circadian model constituent, b) adequately model four major aspects of the 24-h time course of sleep propensity, c) address some unresolved problems with the current model, and d) not conflict with the vast majority of published experimental research.